Protocol and Researcher’s Relationship with Institutional Review Board (African Journal of Biomedical Research, 2020)
The document of ethical approval is an important official requirement for research involving human participants worldwide. It is the process whereby an investigator submits the full research proposal and related documents including detailed informed consent process to an independent Institutional Review Board (IRB) for scrutiny. The process of seeking review and approval is necessary to ensure adequate measure are in place to safeguard and protect research participants as entrenched in the principles of The Declaration of Helsinki and The Belmont Report. It is the responsibility of every clinical researcher to obtain ethical approval, therefore, their obligation to understand the process of review and establish relationship with local IRB in order to enhance smooth review and approval. This article, therefore, explains clinical research and distinguishes between research and clinical care, clarifies briefly what constitutes a study protocol and describes the researchers ' relationship with IRB.